Coach Strategies to Enhance Athletes’ Psychological Readiness for Competition - Ince Abdul Muhaemin; Wardhani, Rio Wakhid Hujjatul Islam; Andi Syaiful; Marsuki (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Objectives. This study examined whether structured coaching strategies can improve athletes’ psychological readiness for competition. Psychological readiness—such as self-confidence, emotional control, concentration, and the ability to manage anxiety—is widely seen as an important factor that supports competitive performance. Materials and Methods. A quasi-experimental pretest–posttest control group design was used. Forty competitive athletes (16–20 years old) were randomly assigned to an intervention group (n = 20) or a control group (n = 20). The intervention was a six-week psychological coaching program that included goal setting, imagery practice, positive self-talk, and pre-competition routines. Psychological readiness was assessed using the Competitive State Anxiety Inventory-2 (CSAI-2) and a validated Psychological Readiness Scale. Data were analyzed with paired and independent sample t-tests, and the effect size was reported using Cohen’s d. Results. Athletes in the intervention group showed a clear improvement in overall psychological readiness after the program (p < 0.01). They also reported lower cognitive and somatic anxiety, along with higher self-confidence. In contrast, the control group did not show meaningful changes (p > 0.05). The overall improvement in psychological readiness produced a large effect size (d = 0.89). Conclusions. The findings indicate that structured psychological coaching strategies can meaningfully strengthen athletes’ psychological readiness for competition. Coaches are encouraged to include mental skills training as part of regular practice to support athletes’ performance in competition.